Polycrystalline MnGe2 thin films on InAs(001) substrates - Gutierrez-Naranjo, David; Holguin-Momaca, Jose T.; Solis-Canto, Oscar O.; Gupta, Preeti; Poddar, Pankaj; Espinosa Magana, Francisco; Olive-Mendez, Sion F. (Thin Solid Films, 2018)
We report on the growth of MnGe2 thin films on InAs(001) substrates using radio frequency-magnetron cosputtering. Polycrystalline thin films were obtained at a substrate temperature of 353 K. X-ray diffractometry was used to identify the tetragonal MnGe2 phase (space group 14/mcm). Measurements of the magnetic field and temperature dependence of the magnetization revealed that the MnGe2 thin films are ferromagnetic with a magnetization of 280 kAm(-1) and a Curie temperature of 62 K. Additionally, an antiferromagnetic component is observed at low temperatures, which may arise atomic disorder at the grain boundaries between MnGe2 crystallites.